Incidence of physical weathering by salt growing deterioration process associated to the aggregates employed in the architectural structures of the Riobamba City - Hernández Mendoza, Jhonnatan Andrés (2024)
Riobamba known as "La ciudad bonita" is one of the emblematic cities of Ecuador, being a tourist attraction for both national and foreign visitors; however, the deterioration of civil works due to the action of salts (haloclasty), can endanger the attractiveness of the city. Walking through the main streets of the city it is easy to see that the formation of salts on the facades of buildings is a recurring problem. Despite this, no study has been carried out to determine which are the main mineral phases responsible for the deterioration of civil works, as well as which and how they are affected. This work aims to show the level of incidence of physical weathering caused by the salt formation process in the architectural works of the city of Riobamba and its relationship with the different aggregates used in each of the mortars and concretes necessary for each one of the structures. For this goal, it was first necessary to establish the current degree of deterioration of the architectural works, in addition to the origin of the materials used in their construction. Subsequently, a sampling of the salts responsible for the deterioration was carried out. Finally, the mineral phases were determined using X-ray diffraction analysis (XRD). The analysis of thirty-two samples, collected in the sector known as El Retamal, allowed us to establish that the main mineral phases responsible for the deterioration of civil works in the city of Riobamba correspond to: thenardite, calcite and nitratine.